2005
DOI: 10.1253/circj.69.861
|View full text |Cite
|
Sign up to set email alerts
|

Reoperation for Ascending Aortic Aneurysm, Coronary Ostial Aneurysm and Patent Cabrol Trick After Bentall Operation for Aortitis Syndrome

Abstract: ortitis is chronic inflammation of the aorta, its branches and the pulmonary artery that leads to stenosis/occlusion or dilatation. Cardiovascular complications, such as aortic regurgitation and aneurysmal dilatation of the aortic root, can be fatal. The most serious complication after aortic valve replacement (AVR) or root reconstruction for aortitis syndrome is dehiscence of the anastomotic site. We report a patient with aortitis syndrome associated with ulcerative colitis who underwent the Bentall operation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…The inclusion technique, as originally described by Bentall and De Bono1 was until 1993 our preferred method. Many authors had reported a relationship between the inclusion/wrapping technique, and the formation of coronary pseudoaneurysm, especially in patients with Marfan syndrome 11-14. The incidence of pseudoaneurysms with this technique ranged from 7% to 25% 15-17.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion technique, as originally described by Bentall and De Bono1 was until 1993 our preferred method. Many authors had reported a relationship between the inclusion/wrapping technique, and the formation of coronary pseudoaneurysm, especially in patients with Marfan syndrome 11-14. The incidence of pseudoaneurysms with this technique ranged from 7% to 25% 15-17.…”
Section: Discussionmentioning
confidence: 99%
“…18-21 In contrast, in young individuals, the acquired factors causing aortic diseases are slightly different, including hypertension from young age, sleep apnea syndrome, pregnancy, steroid use, aortitis, etc. [22][23][24][25][26][27] In the present study, 3 cases of aortitis were observed among the first 129 patients before exclusion of some patients. Among the 29 probands in the non-definite MFS group, 3 obstructive sleep apnea cases including 1 with ACTA2 mutations, and 1 pregnancy with ACTA2 mutations, were found.…”
Section: Discussionmentioning
confidence: 81%
“…Shiono et al 7 described a case of aneurysmal dilatation of the coronary artery ostium without dehiscence of the anastomotic suture line 5 years after a Bentall procedure. The patient presented with both distal anastomotic dehiscence of the Dacron graft with paravalvular leakage, and an aneurysm of the coronary ostium.…”
Section: Discussionmentioning
confidence: 99%